2006
DOI: 10.1002/ar.a.20395
|View full text |Cite
|
Sign up to set email alerts
|

Human cranial anatomy and the differential preservation of population history and climate signatures

Abstract: Cranial morphology is widely used to reconstruct evolutionary relationships, but its reliability in reflecting phylogeny and population history has been questioned. Some cranial regions, particularly the face and neurocranium, are believed to be influenced by the environment and prone to convergence. Others, such as the temporal bone, are thought to reflect more accurately phylogenetic relationships. Direct testing of these hypotheses was not possible until the advent of large genetic data sets. The few releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
390
5
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(437 citation statements)
references
References 33 publications
(60 reference statements)
33
390
5
9
Order By: Relevance
“…However, the high Fst values observed in these variables were mostly influenced by populations living in the northernmost regions of the planet, i.e., extreme North America, Northeast Asia, and Northern Europe. This result agrees with previous studies that found no correlation between climate and cranial morphology once Arctic samples were removed from the analyses and that suggested that climatic adaptation was observed in populations living under extreme cold conditions (Roseman, 2004;Harvati and Weaver, 2006b). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the high Fst values observed in these variables were mostly influenced by populations living in the northernmost regions of the planet, i.e., extreme North America, Northeast Asia, and Northern Europe. This result agrees with previous studies that found no correlation between climate and cranial morphology once Arctic samples were removed from the analyses and that suggested that climatic adaptation was observed in populations living under extreme cold conditions (Roseman, 2004;Harvati and Weaver, 2006b). …”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, the facial measurements in the present study were found to be correlated, albeit more weakly than neurocranial measurements, with geographic distances as well as with climate. This result supports the recent finding by Smith (2009), who reported that facial morphology was correlated with neutral genetic distances (contra Harvati and Weaver, 2006b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In recent decades, it has become clear that the majority of modern human cranial shape variation is congruent with a null model of neutral evolution, with relatively few morphological regions being subject to diversifying selection (e.g., [10][11][12][13][14][15][16][17][18][19]. However, there appear to be two major exceptions to this general pattern.…”
mentioning
confidence: 99%
“…However, there appear to be two major exceptions to this general pattern. Aspects of facial morphology, and particularly nasal morphology, are likely to have been subject to diversifying natural selection in response to climatic conditions (11,(20)(21)(22), which would explain why facial shape is correlated with climate when cold-adapted populations are included (13,18). Second, it has been found (14,15) that global patterns of mandibular variation do not follow a model of neutral evolution.…”
mentioning
confidence: 99%